Answer:
Your hands full
Step-by-step explanation:
Let's solve your equation step-by-step.
Question 1: −2(6−2x) =4(−3+x)
Step 1: Simplify both sides of the equation.
−2(6−2x) =4(−3+x)
(−2) (6) +(−2) (−2x) =(4)(−3)+(4)(x)(Distribute)
−12+4x=−12+4x
4x−12=4x−12
Step 2: Subtract 4x from both sides.
4x−12−4x=4x−12−4x
−12=−12
Step 3: Add 12 to both sides.
−12+12=−12+12
0=0
Answer: All real numbers are solutions.
Question 2:
Let's
solve your equation step-by-step.
5−1(2x+3)
=−2(4+x)
Step 1:
Simplify both sides of the equation.
5−1(2x+3)
=−2(4+x)
5+(−1)
(2x) +(−1) (3) =(−2) (4)+(−2)(x)(Distribute)
5+−2x+−3=−8+−2x
(−2x)
+(5+−3) =−2x−8(Combine Like Terms)
−2x+2=−2x−8
−2x+2=−2x−8
Step 2:
Add 2x to both sides.
−2x+2+2x=−2x−8+2x
2=−8
Step 3:
Subtract 2 from both sides.
2−2=−8−2
0=−10
Answer: There are no solutions.
Y = 54 if your solving for y
Answer:
The correct answer is the length is 10 feet and width is 2 feet respectively.
Step-by-step explanation:
Let length of the rectangular floor of Louis' basement be l feet and width be feet respectively.
Area of the basement floor is given to be 500 square feet.
Therefore according to the given problem,
l × = 500
⇒ = 100
⇒ l = 10 ; [length cannot be negative]
⇒ b = 2
Thus the length and width be 10 feet and 2 feet respectively.
Answer:
a picture would help
Step-by-step explanation:
you need a picture to further understand and answer the question right